Air traffic control radar interference event in the Galileo E6 band: Detection and localization. Issue 3 (30th June 2019) - Arribas, Javier; Vilà‐Valls, Jordi; Ramos, Antonio; Fernández‐Prades, Carles; Closas, Pau
Abstract: The Galileo E6 band operates at a nonprimary frequency band within the L‐band. This presents challenging situations in the vicinity of other, legitimate, radiolocation services. This is the case for Air Traffic Control (ATC) radar, which is seen as an in‐band–pulsed interference by a GNSS receiver. This paper provides a detailed study of the impact of such interference, as well as localization approaches. Particularly, the paper describes the ATC jamming event captured on a GNSS permanent station, its effects on a real receiver, and how it was tracked to localize the source of interference. An ultra low‐cost array‐based solution is prototyped, based on commercial off‐the‐shelf devices, that implements a two‐element array. Experimental results are shown and discussed using real data, validating the localization performance of the prototype.